2021
DOI: 10.3390/ijerph18116055
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drinks Consumption Associated with Emotional and Behavioural Problems via Lack of Sleep and Skipped Breakfast among Adolescents

Abstract: The aim of our study was to explore whether energy drink consumption is associated with both emotional and behavioural problems and whether this association might be mediated by amount of sleep and breakfast consumption among adolescents. The nationally representative Health Behaviour in School-aged Children (HBSC) study, realised in 2018 in Slovakia in schools, was used to acquire needed data, with the research sample of 8405 adolescents from 11 to 15 years old (mean age = 13.43; 50.9% boys) who completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
1
11
1
5
Order By: Relevance
“…As both sleep onset and sleep offset were shifted later following caffeinated beverage consumption in the current study, there was no net effect on sleep duration. Previous studies examining the link between caffeine consumption and self-reported sleep duration in adolescents have been mixed [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 ], while two studies that measured sleep through actigraphy as in the current study found no cross-sectional association between caffeine consumption and sleep [ 21 , 22 , 23 ]. It is possible that self-reported and objectively measured sleep duration capture different constructs, and that adolescents who consume more caffeine perceive their sleep to be shorter without an actual difference in sleep duration.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…As both sleep onset and sleep offset were shifted later following caffeinated beverage consumption in the current study, there was no net effect on sleep duration. Previous studies examining the link between caffeine consumption and self-reported sleep duration in adolescents have been mixed [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 ], while two studies that measured sleep through actigraphy as in the current study found no cross-sectional association between caffeine consumption and sleep [ 21 , 22 , 23 ]. It is possible that self-reported and objectively measured sleep duration capture different constructs, and that adolescents who consume more caffeine perceive their sleep to be shorter without an actual difference in sleep duration.…”
Section: Discussioncontrasting
confidence: 67%
“…Specifically, for every extra SD -hour of variability in sleep duration and midpoint, adolescents were 17% and 21% more likely to consume at least one caffeinated beverage on average across monitoring days. We also measured sleep through objective measures, unlike previous studies that measured sleep through self-report [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 39 ]. Variable sleep schedules may contribute to daytime sleepiness due to circadian misalignment [ 60 ], which could lead to increased caffeinated beverage consumption to maintain alertness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations